The Impact of Social Media on Youth In North West India With Special Reference To Uttarakhand - Dr. Amit Kr. Uniyal, Dr. Anil Kumar Dixit (International Journal of Advanced Science and Technology, 2020)
This research examined the relationship between stress, anxiety level of youth of Uttarakhand (hilly state in north west India ) and youth below the age of 28 years. (focus was on youth higher education) The social media like Instagram, Whatsapp, Facebook, Snapchat, Wechat etc. are widely used with a very rapid growth in India as a result it also gave a number of problems to the youth like anxiety, stress, depression etc.  Secondary and primary data were considered. Sample size of 372 was feasible to be considered.  The constructs were analyzed i.e. time consuming, comparison of lifestyle with others, addiction of use of social media and status consciousness with different age groups and genders. The analysis based on the data shows there is not much difference between the male, female and stress, anxiety level of youths due to social media. Keywords: Social Media, addiction; mental health; anxiety, stress